2012
DOI: 10.1017/s1049096511002113
|View full text |Cite
|
Sign up to set email alerts
|

Learning Political Science with Prediction Markets: An Experimental Study

Abstract: Prediction markets are designed to aggregate the information of many individuals to forecast future events. These markets provide participants with an incentive to seek information and a forum for interaction, making markets a promising tool to motivate student learning. We carried out a quasi-experiment in an introductory political science class to study the effect of prediction markets on student engagement with the course topics. Although we found no significant improvement in students' enthusiasm or extent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…PMs have been positioned as educational tools with applications in a range of domains (see, for example, Buckley, Garvey, & McGrath, 2011;Ellis & Sami, 2012;Evans, 2012;Garvey & Buckley, 2010;Raban & Geifman, 2010). This study uses a carefully designed online PM learning intervention that instantiates all the key elements of gamification.PMs have objective rules.…”
Section: Gamified Learning Interventionmentioning
confidence: 99%
“…PMs have been positioned as educational tools with applications in a range of domains (see, for example, Buckley, Garvey, & McGrath, 2011;Ellis & Sami, 2012;Evans, 2012;Garvey & Buckley, 2010;Raban & Geifman, 2010). This study uses a carefully designed online PM learning intervention that instantiates all the key elements of gamification.PMs have objective rules.…”
Section: Gamified Learning Interventionmentioning
confidence: 99%
“…Moreover, none of the studies we have found approach the use of a prediction market in the same way as we did. Ellis and Sami (2012) create a prediction market for their class on war in international relations. In doing so, they utilize a variety of current events for the students to bet on ranging from the Iranian nuclear weapons test in 2010 to legislative elections in Haiti that same year.…”
Section: Prediction Markets In Political Sciencementioning
confidence: 99%
“…They randomly assigned a subset of their class to trade on the market they built themselves. Ellis and Sami (2012) selected topics to open and close at different points throughout the semester; they also used a virtual currency, internal to their market, that they translated into real money as an incentive for their students at the conclusion of the simulation.…”
Section: Prediction Markets In Political Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…A full description of the experiment and results is forthcoming [Ellis and Sami 2012]; a short preliminary version appeared in the proceedings of the Computer Supported Collaborative Learning (CSCL) 2011 conference [Ellis and Sami 2011]. In contrast to most prior empirical research on prediction markets, which has focused on market outcomes and accuracy, we concentrate on the effect of the market on the traders themselves, as well as on characterizing the self-selected group of traders within the larger group of potential traders.…”
mentioning
confidence: 99%